The long-lasting expression of recombinant artLCMV following intraperitoneal administration exerts potent antitumor effects on tumor models of peritoneal carcinomatosis - Celia Gomar; Aline Risson; Leire Arrizabalaga; Nuria Ardaiz; Virginia Belsue; Adrian Gil-Korilis; Sarah Ahmadi-Erber; Timo Schippers; Ignacio Melero; Klaus K. Orlinger; Fernando Aranda; Henning Lauterbach; et al. (OncoImmunology)
Peritoneal carcinomatosis remains a challenging clinical condition with limited therapeutic options. In this study, we evaluated the efficacy of a recombinant artLCMV platform encoding tumor antigens and immune-stimulatory molecules in preclinical models. We analyzed the expression kinetics, biodistribution, and antitumor activity of artLCMV vectors encoding the reporter protein NanoLuc, tumor-associated antigens such as gp70 or folate receptor alpha (FRα), and immune-stimulatory molecules including IL12 or 4-1BBL. These vectors were tested in murine models of peritoneal carcinomatosis established by intraperitoneal inoculation of MC38 colon cancer cells or ID8-VEGF ovarian cancer cells. Intraperitoneal administration of artLCMV-NanoLuc resulted in sustained, high-level transgene expression in the peritoneal cavity for over 40 days. The antitumor efficacy of artLCMV.gp70 was significantly enhanced by IL12, eliciting a robust immune response in the MC38 model. In contrast, artLCMV.gp70 and artLCMV.FRα effectively reduced tumor burden and prolonged survival in ID8-VEGF mice, but coexpression of IL12 or 4-1BBL did not provide additional therapeutic benefit. These findings demonstrate that recombinant artLCMV vectors offer a promising therapeutic strategy for peritoneal carcinomatosis, delivering long-lasting transgene expression and potent antitumor effects. The addition of immunostimulatory molecules such as IL12 may enhance efficacy in certain tumor models, though its effects appear to be context-dependent.